Global Challenges in Radiation Oncology - Daniel Grant Petereit (Frontiers Research Topics, 2015)
In the United States, much of the research is focused on developing new and very expensive technologies and drugs - often without a major therapeutic benefit. In resource limited countries, basic oncology care is frequently lacking. In addition, the benefits of various chemo-radiotherapy combinations for a number of malignancies are unknown as these populations have not been adequately investigated. For oncologists in these countries who have marginal to adequate resources, accrual to clinical trials is virtually non-existent to minimal, due to the complexities of their population and competing co-morbidities. As a result, there is a tremendous disparity in treatment outcomes for these populations, compared to those in developed countries. Therefore, we have asked a number of oncologists from different parts of the world to report their experience. Topics that will be covered include locally advanced breast and cervical cancer (India, South Africa), human resources for cancer control in India, systematic review of radiation resources in low and middle income countries, planning national radiotherapy services, building sustainable partnerships through the newly formed ICEC (International Cancer Export Corps), cancer disparities among American Indians, and training radiation oncologists in these under served parts of the world. Authors will discuss "lessons learned" from their populations, practical suggestions to address these disparities, and how we as a global oncology community can address, and mitigate these global challenges. The editorial by Dr. Coleman and myself highlights the invaluable contributions from our global contributors. Thank you for taking the time to read this special issue on global cancer disparities. We are all energized to begin addressing the needs of our cancer patients worldwide.